Isolation of a high‐affinity Bet v 1‐specific IgG‐derived ScFv from a subject vaccinated with hypoallergenic Bet v 1 fragments - Gadermaier, E.; Marth, K.; Lupinek, C.; Campana, R.; Hofer, G.; Blatt, K.; Smiljkovic, D.; Roder, U.; Focke‐Tejkl, M.; Vrtala, S.; Keller, W.; Valent, P.; et al. (Allergy (Copenhagen), 2018)
Background Recombinant hypoallergenic allergen derivatives have been used in clinical immunotherapy studies, and clinical efficacy seems to be related to the induction of blocking IgG antibodies recognizing the wild‐type allergens. However, so far no treatment‐induced IgG antibodies have been characterized. Objective To clone, express, and characterize IgG antibodies induced by vaccination with two hypoallergenic recombinant fragments of the major birch pollen allergen, Bet v 1 in a nonallergic subject. Methods A phage‐displayed combinatorial single‐chain fragment (ScFv) library was constructed from blood of the immunized subject and screened for Bet v 1‐reactive antibody fragments. ScFvs were tested for specificity and cross‐reactivity to native Bet v 1 and related pollen and food allergens, and epitope mapping was performed. Germline ancestor genes of the antibody were analyzed with the ImMunoGeneTics (IMGT) database. The affinity to Bet v 1 and cross‐reactive allergens was determined by surface plasmon resonance measurements. The ability to inhibit patients’ IgE binding to ELISA plate‐bound allergens and allergen‐induced basophil activation was assessed. Results A combinatorial ScFv library was obtained from the vaccinated donor after three injections with the Bet v 1 fragments. Despite being almost in germline configuration, ScFv (clone H3‐1) reacted with high affinity to native Bet v 1 and homologous allergens, inhibited allergic patients’ polyclonal IgE binding to Bet v 1, and partially suppressed allergen‐induced basophil activation. Conclusion Immunization with unfolded hypoallergenic allergen derivatives induces high‐affinity antibodies even in nonallergic subjects which recognize the folded wild‐type allergens and inhibit polyclonal IgE binding of allergic patients.